Racial Segregation in the Southern Schools, School Districts, and Counties Where Districts Have Seceded. (July 2019) - Taylor, Kendra; Frankenberg, Erica; Siegel-Hawley, Genevieve
The establishment of new school districts in predominantly White municipalities in the South is restructuring school and housing segregation in impacted countywide school systems. This article compares the contribution of school district boundaries to school and residential segregation in the Southern counties that experienced secession since 2000. Merging together several data sets, including Common Core of Data, census data, and shapefiles at multiple geographic scales, we measure segregation of public school students and the entire population over time. We show that school district secession is restructuring school segregation in the counties where secession is occurring, with segregation increasingly occurring because students attend different school districts. Additionally, in the most recent year of analysis, residents were increasingly stratified by race in different school districts. Segregation patterns differ substantially, however, depending on the history of secession in the county.